Visible absorbing symmetrical squaraine and croconine dye derivatives: A comparative computational study. (12th December 2016) - Tripathi, Anuj; Promila,; Prabhakar, Chetti
Abstract: Visible absorbing C–N bonding squaraines (SQ1‐SQ5) and croconines (CR1‐CR5) with an increase in conjugation at donor groups and heteroaromatic donor substituents have been studied by density functional theory and time‐dependent density functional theory methodologies. In these molecules, croconines always have absorption nearly 100‐nm red shift than its corresponding squaraines (it is in consistent with C–C bonding, near infrared absorbing squaraine and croconines). The reason behind this drastic red shift, by changing the central acceptor of 4‐membered squarate ring with 5‐membered croconate ring, has been analyzed by considering the concept of diradical character and variation in central C–C–C angle. It is also observed that within the same series of molecules (either in squaraine or in croconines), with an increase in donor capacity (conjugation), absorption increases towards longer wavelength region because of destabilization of HOMO and stabilization of LUMO levels. A small blue shift was observed for heteroaromatic donor groups when compared with aromatic donor group. Abstract : C–N bonding croconine molecules are having approximately 100‐nm red shifted absorption than its corresponding squaraines. This red shifted absorption in croconines is due to the variation in central C–C–C angle (replacement of central 4‐membered ring with 5‐membered ring) and presence of some diradical character (squaraines are showing zero diradical character, and croconines are found with some diradical character, ranging from 18% to 25%). Enhanced optical absorption was also observed in same series of molecules (either in squaraines or in croconines) with increase in conjugation at donor group.